A Facile Synthesis of 3‐Substituted Coumarins and Investigation of Their 3CLpro Inhibition Activity Against SARS‐CoV‐2 - Manoj K. Choudhary; Khalid Ansari; Vivek Junghare; Sandip K. Nayak; Saugata Hazra; Soumyaditya Mula (ChemistryOpen)
Abstract The major threat to public health due to the outbreak of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection has been recognised as a global issue. The increase in morbidity is primarily due to the lack of SARS‐CoV‐2 specific drugs. One of the major strategies to combat this threat is to deactivate the enzymes responsible for the replication of corona virus. To this end, 3‐arylidene/3‐hydroxycoumarin induced deactivation of 3‐chymotrypsin like protease (3CLpro) enzyme, which takes the pivotal role in the replication and maturation, was investigated. For ready availability of the compounds for the above investigation, we have developed a user‐friendly protocol for the synthesis 3‐hydroxycoumarin derivatives from cheap and readily available starting materials in two steps; i) Bronsted acid catalysed Friedel‐Crafts alkylation of phenols with Morita‐Baylis‐Hillman adducts followed by intramolecular lactonization to trans‐3‐arylidenechroman‐2‐ones in one‐pot and ii) ozonolysis in reasonably good yields. Pharmacokinetic assessments of coumarin derivatives revealed drug‐like characteristics with moderate or low toxicity values. Notably, these hydroxycoumarins exhibited enhanced binding affinity against the 3CL protease of SARS‐CoV‐2, fitting well into the binding pocket akin to the previously studied inhibitor N3. Furthermore, a molecular dynamics study elucidated the dynamic behaviour of these small molecules when bound to the protein, showcasing intriguing complexities within the active site. Despite backbone variations and residual fluctuations, compounds 3 d–f and 6 a exhibited a consistent behaviour, instilling confidence in the therapeutic potential of these coumarins for combating SARS‐CoV‐2.